Railroad Vine: Ipomoea pes-caprae, a Florida Native Plant - Stephen H. Brown; Joy Hazell (EDIS)
ENH1157, a 7-page illustrated fact sheet by Stephen H. Brown and Joy Hazell, describes this pantropic vine found on beaches and dunes throughout peninsular Florida — geographic distribution, ecological function, growth habit, morphology and reproduction, and planting and maintenance guidelines. Includes references. Published by the UF Department of Environmental Horticulture, February 2010.